БЮДЖЕТНА ДЕЦЕНТРАЛІЗАЦІЯ Й ЕКОНОМІЧНИЙ РІСТ РЕГІОНІВ УКРАЇНИ: АНАЛІЗ ТА ОЦІНКА (Світ фінансів, 2017)
Возняк Г. В. Бюджетна децентралізація й економічний ріст регіонів України: аналіз та оцінка. Проведено огляд існуючих підходів до оцінки впливу бюджетної децентралізації на економічний ріст регіонів. Проаналізовано можливі напрями вибору ключових чинників, які визначають ступінь децентралізації як в окремих країнах, так і в межах однієї країни в розрізі її адміністративних одиниць. Виокремлено проблеми оцінювання рівня бюджетної децентралізації. На основі запропонованого підходу в роботі проведено просторово-динамічну оцінку впливу бюджетної децентралізації на економічний ріст регіонів України. Возняк Г. В. Бюджетная децентрализация и экономический рост регионов Украины: анализ и оценка. Проведен обзор существующих подходов к оценке влияния бюджетной децентрализации на экономический рост регионов. Проанализированы возможные направления выбора ключевых факторов, определяющих степень децентрализации как в отдельных странах, так и в пределах одной страны в разрезе ее административных единиц. Обозначены проблемы оценки уровня бюджетной децентрализации. На основе предложенного подхода проведена пространственно-динамическая оценка влияния бюджетной децентрализации на экономический рост регионов Украины. Voznjak H. Budgetary decentralization and economic growth of the regions of Ukraine: analysis and evaluation. Introduction. The issues of budgetary decentralization in recent years are at the epicenter of attention of economics due to the fact that it allows to increase the efficiency of usage of budget funds to improve the quality of social services and to approach them to the needs of community, although there is a lot of risk of strengthening budgetary decentralization. Considering the fact that this phenomenon has many aspects, actualization of the issue becomes especially important: qualitative and quantitative methods of its measurement and evaluation; impact on social and economic processes and establishing of closeness of the interconnection of factors that determine them.Purpose. The purpose of the article is analysis, spatial and dynamic assessment of the impact of budgetary decentralization on economic growth of the regions of Ukraine.Results. The conducted analysis of existing approaches to quantitative estimation of the impact of budgetary decentralization on economic growth of the regions shows a dominance of approaches to assessment of budgetary decentralization with the usage of time series (or panel data) for a sample of countries or regions, while using typical methods - standard regression, least squares method, as well as fixed and random effects. On the basis of theoretical achievements, analytical assessment and the proposed methodological approach, in the work there was conducted empirical analysis and assessment of budgetary decentralization in Ukraine, with the usage of panel data (there were surveyed 27 regions of Ukraine for 9 years). The assessment of the level of decentralisation was carried out by four directions: a formation of revenues of the local budgets; a financing of expeditures; an implementation of interbudgetary relations and the level of tax burden.Conclusions. As a result of the conducted study, the author proved the ambiguous nature of budgetary decentralization and identified signifi cant factors of influence. It is shown that regional budgetary decentralization by level of tax burden is negatively and significantly associated with economic growth of the regions; a dependence of the regional development on interbudgetary transfers is positively associated with growth, while budgetary decentralization, by expenditures, negatively affects the growth of GRP, which indicates that, on the one hand, the expeditures are excessively centralized and they are not agreed with the revenues, on the other hand , about the lack of incentives of local authorities to effective spending of budgetary funds.